A National Dental Practice-Based Research Network phase II, cluster-randomized clinical trial assessing nicotine replacement therapy sampling in dental settings: study protocol for the Free Samples for Health (FreSH) study - Pearl Fang; Melissa Adkins-Hempel; Tamara Lischka; Sarah Basile; D. Brad Rindal; Matthew J. Carpenter; Dorota T. Kopycka-Kedzierawski; Jennifer Dahne; Sarah A. Helseth; Douglas E. Levy; Arthur Truong; Michael C. Leo; et al. (BMC, 2024)
Abstract Background Cigarette smoking has major detrimental effects on oral health. Tobacco interventions in dental settings are effective, but rarely delivered. The American Dental Hygienists Association recommends that oral health providers: Ask patients about tobacco use, Advise quitting tobacco use, and Refer to state quitlines (Ask-Advise-Refer; AAR). While AAR connects patients to counseling, it does not directly connect patients to medication. Nicotine replacement therapy sampling (NRTS) is an empirically supported intervention to provide starter packs of nicotine replacement therapy (NRT) to people who smoke. NRTS combined with AAR could be an effective tobacco treatment intervention for dental settings. Methods This manuscript describes the study protocol for the Free Samples for Health (FreSH) study, a group randomized clinical trial testing the effectiveness of NRTS + AAR vs. AAR alone on long-term smoking abstinence. Fifty dental practices in the Midwest and Northeast nodes of the National Dental Practice-Based Research Network are randomly assigned to provide AAR and either a 2-week supply of 14-mg nicotine patches and 4-mg nicotine lozenges (NRTS condition) or an electric toothbrush (ET condition). Approximately 1,200 patients who currently smoke-regardless of interest in quitting- are recruited during dental visits. Participants complete a baseline survey in-person, then after visit, 1-, 3-, and 6-month follow-up surveys remotely. The primary outcome is carbon monoxide-confirmed 7-day point prevalence abstinence from combustible tobacco measured at 6 months post-enrollment. Secondary outcomes include: 24-h intentional quit attempts, change in cigarettes smoked per day, NRT utilization, attitudes toward NRT, intention to use NRT, and intention to quit smoking. A key informant process evaluation and cost effectiveness analysis will provide information for future implementation of NRTS. Discussion This is the first clinical trial to assess the effectiveness of NRTS on promoting smoking cessation in dental settings. If effective, this treatment could be implemented to increase the provision of smoking cessation interventions in dental settings to provide an additional treatment access point for people who smoke. Trial Registration. Registered at ClincalTrials.gov (NCT05627596) on 11/25/2022.